Let's take the long way home : a memoir of friendship - Caldwell, Gail, 1951- (Random House, 2010)
In this moving memoir, Pulitzer Prize-winning author Caldwell reflects on her own coming-of-age in midlife, as she learns to open herself to the power and healing of sharing her life with a best friend.